2021
DOI: 10.1002/anie.202109519
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Controlled Stereoselective Barton–Kellogg Olefination

Abstract: Overcrowded alkenes are expeditiously prepared by the versatile Barton–Kellogg olefination and have remarkable applications as functional molecules owing to their unique stereochemical features. The induced stereodynamics thereby enable the controlled motion of molecular switches and motors, while the high configurational stability prevents undesired isomeric scrambling. Bistricyclic aromatic enes are prototypical overcrowded alkenes with outstanding stereochemical properties, but their stereocontrolled prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…The elaborations of some enantioenriched thiiranes were also carried out. Unfortunately, it was found that tetrasubstituted alkenes D1 – D4 via desulfuration of thiirane C1 or C33 , namely Barton–Kellogg olefination, [4c, 14] were afforded in decent results under varied conditions (Scheme 2c, see the Supporting Information for details). These results indicate that the high tense strain of the 3‐membered ring of thiirane was more likely to be released via desulfuration, [4c, 6] rather than substitution reaction, ring opening or expansion [15] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The elaborations of some enantioenriched thiiranes were also carried out. Unfortunately, it was found that tetrasubstituted alkenes D1 – D4 via desulfuration of thiirane C1 or C33 , namely Barton–Kellogg olefination, [4c, 14] were afforded in decent results under varied conditions (Scheme 2c, see the Supporting Information for details). These results indicate that the high tense strain of the 3‐membered ring of thiirane was more likely to be released via desulfuration, [4c, 6] rather than substitution reaction, ring opening or expansion [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it was found that tetrasubstituted alkenes D1 – D4 via desulfuration of thiirane C1 or C33 , namely Barton–Kellogg olefination, [4c, 14] were afforded in decent results under varied conditions (Scheme 2c, see the Supporting Information for details). These results indicate that the high tense strain of the 3‐membered ring of thiirane was more likely to be released via desulfuration, [4c, 6] rather than substitution reaction, ring opening or expansion [15] . Of note, the tetrasubstituted olefins D3 and D4 were obtained in high E / Z selectivity when thiirane C33 with high diastereoselectivity was employed [16] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain derivatives of 4,5-diazafluorene belong to the group of the so-called bistricyclic aromatic enes (BAEs). BAEs and related polycyclic systems are a class of molecular materials that display a rich variety of conformations, dynamic stereochemistry and switchable chirality, color, and spectroscopic properties [43][44][45]. The chelating fragment of 4,5-diazafluorene incorporated into an overcrowded alkene molecule leads to new, unusual properties of the transition metal complexes [42,46].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the episulfidation of alkenes has been investigated 15 , but this seemingly straightforward epoxidation-like approach is applicable only to a limited range of cyclic alkenes. Otherwise, stereoselective synthesis of thiiranes has rarely been developed [41][42][43][44][45] , and most of the reported examples have serious drawbacks such as low stereoselectivity, narrow substrate scope, and/ or the requirement of highly toxic reagents. Among these precedents, a unique synthetic sequence of the Barton-Kellogg reaction is noteworthy (Fig.…”
mentioning
confidence: 99%